2018
DOI: 10.1681/asn.2018050488
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Cancer Immunotherapies: Past, Present and Future

Abstract: Nephrotoxicity from cancer therapies is common and increasingly encountered in clinical practice, such that the subfield of "onco-nephrology" has emerged. Conventional chemotherapeutic drugs and novel agents targeting specific genes/proteins are effective cancer therapies but suffer from a number of adverse kidney effects. An effective avenue of cancer treatment is immunotherapy, which uses drugs that augment immune system-mediated recognition and targeting of tumor cells. As such, leveraging the immune system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 93 publications
2
113
0
6
Order By: Relevance
“…That this might actually be the case in SARS-CoV infection was discovered by a subsequent study that showed that an interferon-gamma-related cytokine storm was induced post-SARS-CoV, leading to severe organ damage in SARS patients [34]. This process is not new to nephrologists, as cytokine-mediated inflammatory AKI has been reported in several clinical conditions, such as treatment with immune-checkpoint inhibitors and chimaeric antigen receptor (CAR) T cells in cancer patients [35], as well as thymoglobulin treatment in renal transplanted patients [36].…”
Section: The Contribution Of Ace2-expressing Organs In Sars-cov-2 Repmentioning
confidence: 96%
“…That this might actually be the case in SARS-CoV infection was discovered by a subsequent study that showed that an interferon-gamma-related cytokine storm was induced post-SARS-CoV, leading to severe organ damage in SARS patients [34]. This process is not new to nephrologists, as cytokine-mediated inflammatory AKI has been reported in several clinical conditions, such as treatment with immune-checkpoint inhibitors and chimaeric antigen receptor (CAR) T cells in cancer patients [35], as well as thymoglobulin treatment in renal transplanted patients [36].…”
Section: The Contribution Of Ace2-expressing Organs In Sars-cov-2 Repmentioning
confidence: 96%
“…The latter hypothesis is based on a previous report that 14 out of 19 ATIN patients, while using ICIs, combined suspected drugs such as proton pump inhibitor (PPI) and NSAIDs for drug-induced interstitial nephritis [11]. Similarly, Perazella et al [12] reviewed nephrotoxicity in cancer immunotherapies and discussed the mechanisms underlying ICI-induced kidney injury. Among them, we consider two hypotheses for the pathogenesis of AKI in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Die Formen renaler Beteiligung durch gesteigerte Autoimmunität bei Checkpoint-Inhibition wurden in den letzten 5 Jahren zunehmend gut beschrieben [19,20]. Aktuell liegen zwei gleichermaßen rezente wie lesenswerte Studien zum Thema vor -die eine von Anker et al, erschienen in der Januarausgabe von Der Nephrologe [21,22].…”
Section: Nierenbeteiligungunclassified